2019
DOI: 10.2147/dmso.s208072
|View full text |Cite
|
Sign up to set email alerts
|

<p>Does a diabetic retinopathy educational program raise awareness among elderly diabetic patients?</p>

Abstract: Background and aim: Diabetic retinopathy is a serious and common complication of diabetes that causes irreversible blindness. The aim of the present study was to assess the knowledge, attitudes, and practice regarding diabetic retinopathy among patients attending a diabetic clinic and identify the effect of an educational program about diabetic retinopathy. Patients and methods: Two hundred diabetic patients were recruited from the outpatient's diabetic clinic, Assiut University hospitals, Egypt. Quasi-experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
8
15
0
Order By: Relevance
“…In the present study, an increase in the attitude of patients with diabetes towards diabetes care has been reported in similar study in Iran [20] and Ontario, Canada [21]. However, there was no change in attitude in Khalaf et al study due to the short duration of training [22] because changing patients' attitudes, unlike their awareness, requires longer intervention. In the study of Grimshaw et al in Ottawa Hospital Research Institute [23] and the study of Zwarenstein et al in London [24], training by providing educational booklets to physicians to increase their attitude towards referring patients for ophthalmological examinations was not so effective.…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, an increase in the attitude of patients with diabetes towards diabetes care has been reported in similar study in Iran [20] and Ontario, Canada [21]. However, there was no change in attitude in Khalaf et al study due to the short duration of training [22] because changing patients' attitudes, unlike their awareness, requires longer intervention. In the study of Grimshaw et al in Ottawa Hospital Research Institute [23] and the study of Zwarenstein et al in London [24], training by providing educational booklets to physicians to increase their attitude towards referring patients for ophthalmological examinations was not so effective.…”
Section: Discussionsupporting
confidence: 57%
“…These study results are similar to a hospital-based study in Egypt that observed the increased DR knowledge. 12 Also, these positive impacts on knowledge level are similar to the other study that used a 'mobile health' intervention that was designed based on the selfdetermination theoretical constructs of the health promotion. 5 The mobile health also observed a positive change in the health behaviour of the community post intervention towards their disease prevention as well as the treatments.…”
Section: Discussionsupporting
confidence: 64%
“…4 Prior studies have been conducted to evaluate the impact of DR educational programmes amongst the diabetic population. 12 However, the effectiveness of various tools have not been directly compared before their implementation within the general population. 4 In summary, because of the increasing prevalence of DM in the Sultanate of Oman, there is a need to enhance the DR related knowledge levels amongst the community.…”
mentioning
confidence: 99%
“…This study also shows that frailty and co-morbidities/DM complications could impair patients’ knowledge. 32 , 33 The explanation for this may be due to functional and cognitive impairment and dependence to perform the activities of daily living, which can be a barrier to improve knowledge in older diabetic patients. In particular, this finding showed that knowledge of patients aged ≄70 was significantly lower than those aged 60 to 69.…”
Section: Discussionmentioning
confidence: 99%